Hereditary C1q deficiency: a new family with C1qA deficiency - Sun-Tan, Cağman; Ozgür, Tuba Turul; Kilinç, Gamze; Topaloğlu, Rezan; Gököz, Ozay; Ersoy-Evans, Sibel; Sanal, Ozden (The Turkish Journal of Pediatrics, 2010)
Hereditary deficiency of complement component C1q is a rare genetic disorder with susceptibility to recurrent infections with polysaccharide-containing encapsulated microorganisms and a high prevalence of autoimmune diseases, most often systemic lupus erythematosus (SLE). Here, we report a 29-month-old boy who presented with facial rash and history of early death of a sibling with infections, who was found to have a selective deficiency of C1q. The facial rash was composed of patchy erythematous plaques and centrally hypopigmented macules and desquamation. Two siblings had died of severe bacterial infections and his uncle had died of meningitis. Molecular study disclosed a homozygous point mutation in the C1qA chain gene. Five members of the family, including the parents and three healthy siblings, were heterozygous for this mutation.